1999
DOI: 10.24266/0738-2898-17.4.193
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination of Rhododendron chapmanii: Influence of Light and Temperature

Abstract: Seeds of Rhododendron chapmanii A. Gray (Chapman's rhododendron) were germinated at 25C (77F) or 8/16 hr thermoperiods of 25/15C (77/59F) or 30/20C (86/68F) with daily photoperiods of 0 (total darkness), ¼, ½, 1, 2, 4, 8, 12 or 24 hr. For all temperatures, no germination occurred during a 30-day period for seeds not subjected to light. At 25C (77F) germination was a function of photoperiod. The longer the photoperiod the greater the germination with 30-day germination ≥90% for photoperiods ≥8 hr. Alternating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Other studies have indicated that photoperiod regulates seed germination of Rhododendron chapmanii A. (Arocha et al 1999), hyssop loosestrife (Lythrum hyssopifolia L.), and corn poppy [Parapholis incurva (L.) Hubbard] (Noe and Zedler 2000) (see also Baskin C. C. and Baskin J. M. 1998;Black 1967). Densmore (1997) found that a combination of short day length and stratification requirement prevents germination of Alaskan plant seed in the fall.…”
Section: Modeling Weed Emergencementioning
confidence: 99%
“…Other studies have indicated that photoperiod regulates seed germination of Rhododendron chapmanii A. (Arocha et al 1999), hyssop loosestrife (Lythrum hyssopifolia L.), and corn poppy [Parapholis incurva (L.) Hubbard] (Noe and Zedler 2000) (see also Baskin C. C. and Baskin J. M. 1998;Black 1967). Densmore (1997) found that a combination of short day length and stratification requirement prevents germination of Alaskan plant seed in the fall.…”
Section: Modeling Weed Emergencementioning
confidence: 99%
“…The average 1000-seed weight of Rhododendron species in Turkey was reported between 0.142 g and 0.067 g (Altun, 2011). The seeds do not need any chilling requirements due to the higher germination and emergence rates, depending upon species (Ryabova and Zueva, 1993;Sakharova, 1993;Arocha et al, 1999;Glenn et al, 1999;Basnet, 2005;Vologdina, 2006;Altun, 2011). Seeds need light to germinate (Vologdina, 2006); therefore, seeds must be sown superficially during planting and not be covered.…”
Section: Introductionmentioning
confidence: 99%
“…Rhododendrons normally produce numerous amounts of seeds (Cox, 1990;Romancier, 1970) [12,48] however; viable seeds are not always available on a yearly basis. They are extremely small and size can vary greatly among species (Arocha et al, 1999;Blazich et al, 1991;Glenn et al, 1998;Olson, 1974) [3,7,20,40] . R. arboreum, locally known as 'Burans', is amongst highly valued wild edible tree growing in hills of HP state found distributed in Shimla, Solan, Kinnaur, Mandi, Kangra, Kullu, Sirmour and Chamba districts of Himachal Pradesh (Kharwal and Rawat, 2013) [25] .…”
Section: Introductionmentioning
confidence: 99%